The Barmen declaration (May 1934) - Rees, Owen Geoffrey (Studies in church history, 1975)
The exposition delivered at the synod of Barmen on Wednesday, 30 May 1934, by Pfarrer Hans Asmussen gives us the exact purpose and intention of the committee which had drawn up the six articles of the theological declaration. It is made quite clear that the fundamental concern of the declaration is divine revelation. In the several articles of the declaration the uniqueness of the revelation in Christ is asserted and the uniqueness of the church as the body which is entrusted with the proclamation of that revelation is equally carefully emphasised. The church is alone in her responsibility and any attempt by the world to usurp that responsibility must be rejected. These great claims for the church are made because the church is more than a sociological entity, and the church must ever remain that which she truly is. Positions of responsibility within the church should be exercised with humility, for thus only can church order correspond to the inner essence of the church. The limits which separate the church and the state must be strictly observed and neither the church nor the state should presume to exercise authority in that which does not belong to it. And finally, the freedom of the Holy Spirit must be known, and the guidance of the Holy Spirit must be felt in the church. These statements are the culmination of a series of events in which the German evangelical church had been seriously disturbed by the national socialist policy of Gleichschaltung. Together with this there had been an attempt in various parts of the church to modify its doctrinal position and in that way to admit elements of racial nationalism. Finally, there had been since the collapse of Germany at the end of the great war a formidable amount of political theology which discovered manifestations of God’s will and purpose otherwise than in the revelation of Jesus Christ. It is these three aspects of the life of the church which created a crisis which brought about the first confessing synod of the German evangelical church at Barmen on 29 to 31 May 1934.